Aggregation of Human Blood Platelets by Remnant Like Lipoprotein Particles of Plasma Chylomicrons and Very Low Density Lipoproteins - Saniabadi, Abby R; Umemura, Kazou; Shimoyama, Makiko; Adachi, Masakazu; Nakano, Minoru; Nakashima, Mitsuyoshi (Thrombosis and Haemostasis, 1997)
Remnant like lipoprotein particles (RLP) of partially catabolised human plasma chylomicrons (CM) and very low density lipoproteins (VLDL) were separated from CM and VLDL using two monoclonal antibodies, anti apo B-100 (JI-H) and anti apo A-I (H-12) coupled to Sepharose 4B gel to form an immunoaffinity column. Lipoproteins containing apo B-100 or apo E, including VLDL and LDL adsorb to (JI-H)-gel, while CM and HDL with apo A-I adsorb to (H-12)-gel. The unbound fraction (RLP) is rich in apo B-48, apo E and apo E rich apo B-100 which has not been recognized by JI-H. The RLP fraction with a total triglyceride of 12.35 ± 6.22 mg/ml; total cholesterol, 0.32 ± 0.08 mg/ml and total protein, 0.72 ± 0.12 mg/ml (mean ± S.E.M, n = 9) was added to blood from healthy persons at 2.5-200 |xl/ml and agitated gently at 37° C for 40 s. Platelet aggregation was assessed by measuring the loss of single platelets. At 2.5-10 μl, RLP induced platelet aggegation increased with the dose of RLP, but decreased at 25-200 julLScanning electron microscopy revealed that within 20 s of agitation in the presence of RLP, activated platelets had appeared on the red cell membrane and within 40 s of agitation, platelet aggregates had formed on the red cells. The platelet responses were unaffected by aspirin (10 or 20 μg/ml) but were inhibited by cilostazol, a phosphodiesterase type III inhibitor (0.4 to 1.6 μg/ml). It is likely that the platelet effect of RLP is a consequence of RLP dependent red cell-platelet interaction. This is the first report of platelet aggregation induced by RLP without an added platelet agonist.